Efectos de la incertidumbre de los precios del petróleo en el crecimiento económico de México - Domingo Rodríguez Benavides; Francisco López Herrera (Investigación Económica, 2019)
– We inquire whether the uncertainty of international oil prices affected Mexico's economic activity during 1983:2-2017:4. To measure such impact we use a bivariate structural vector autoregressive (VAR) model with a generalized autoregressive conditional heteroskedasticity (GARCH) in-mean process that captures the impact of oil price volatility on economic growth and gross fixed capital formation. Our results show that the said uncertainty has a negative influence on Mexico's economic activity. Further, they reveal the presence of asymmetric effects, as the output growth rate increases (decreases) after a negative (positive) oil price shock. These results highlight the importance of adopting public policies aimed at mitigating the effects of oil market uncertainty and help stabilize economic activity.
Keywords: E32; C32; 330; Oil price volatility; economic activity; multivariate var-garch in-mean; asymmetric effects; Mexico